English Vocabulary Mastery Difficulties for Primary School Learners - Nazhira, Najwa; Kania, Diva Adira; Panjaitan, Isma Canda Ningtyas; Ulayya, Salsabil Beli; Amirul, Bani (Madani: Jurnal Ilmiah Multidisiplin, 2024)
English is one of the foreign languages that needs to be mastered to facilitate a person in communicating between countries. Difficulties that are often found in the process of learning English in elementary schools are vocabulary mastery. The original purpose of this study is to find out more about what forms of difficulties experienced by students in vocabulary domination material, find out what factors cause difficulties in vocabulary domination, and find out solutions to handle it.   The researcher used qualitative research methods. The results share that there are many forms of difficulties experienced by elementary school students in mastering English vocabulary, including students who are not familiar with the use of English dictionaries, students lack understanding of English vocabulary in the material presented, students are not accustomed to using English in everyday life, students cannot mention vocabulary, synonyms and antonyms in writing, and students have not been able to write synchronous words with perfect spelling. The difficulties that occur are caused by internal factors as well as external factors.  Efforts that can be made by the teacher to increase students' mastery of English vocabulary are by using media or learning methods such as the Running Dictation method, picture word domino card media, charades game method, Flash Card media, and TPR storytelling method.